Betulinic Acid, The First Lupane‐Type Triterpenoid Isolated from Both a Phomopsis sp. and Its Host Plant Diospyros carbonaria Benoist. Issue 1 (19th December 2016) - Peyrat, Laure‐Anne; Eparvier, Véronique; Eydoux, Cécilia; Guillemot, Jean‐Claude; Litaudon, Marc; Stien, Didier
Abstract : Following a biological screening using a dengue replicon virus‐cell‐based assay, Diospyros carbonaria AcOEt extract was investigated, affording six known lupane‐type triterpenoids endowed with anti‐DENV‐2 NS5 polymerase activity. The study of the associated microbial community of this species permitted us to identify 38 endophytes belonging to five different orders. Nine out of these 38 strains showed significant activity on the dengue replicon assay. The chemical investigation of the most active one, Phomopsis sp. SNB‐LAP1‐7‐32, led to the isolation of betulinic acid, an anti‐viral secondary metabolite isolated previously from the host plant. This result is the first example of a lupane‐type triterpenoid isolated from both an endophyte and its host plant. Its presence in the Phomopsis strain may result from gene transfer and/or specific niche selection. Abstract :